Nutritional Status of Children Under Five Years in the Work Area of Puskesmas Cipadung - Nafia, Zidni Ilma; Shodiq, Istiqomah Zakiyah; Handayani, Lina (Disease Prevention and Public Health Journal, 2021)
Background: Children under five years are in the golden growth and development period; however, an excellent nutritional status must support optimal growth and development. The nutritional status of children under five years needs special attention. An overview of the nutritional status of children in a region is the first step to determine the factors that affect the nutritional status of children under five in that region. Method: This was a descriptive study with a cross-sectional design. Results: The results showed that children under five aged 0 – 23 months were 35.47%, while those aged 24-59 months were 64.53%, boys were 52.95%, and girls were 47.05%. Children under five years with inferior nutritional status (index weight/age) of 2.63%, children with nutritional status of stunting (index for height/age) of 12.57%. Children with a malnutrition status (index weight/height) of 2.41%. Conclusion: The problem of stunting and wasting nutrition is still found in the work area Puskesmas Cipadung. These problems can arise due to poor parenting and lack of nutritious food intake due to parents' low education and income level.